A note on Germany's role in the fourth industrial revolution - Vanessa Behrens; Steffen Viete (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2020)
This paper provides in-depth insights into patenting activities in technologies of the Fourth Industrial Revolution (4IR) in Germany and worldwide between the years 1990 and 2016. The descriptive analysis of these digital inventions at the current technological frontier yields several main findings. Germany is a leader in 4IR innovations, accounting for 12% of all 4IR patents filed wordwide. Digital inventions are predominantly filed in the ICT sector, yet compared to other 4IR leaders, Germany's 4IR patents are relatively more directed to the motor vehicles sector and less so to the ICT sector. This is driven by Germany's high R&D-intensity in this sector, rather than a larger share of 4IR inventions in the motor vehicle sector. Germany's leading position is driven by its high number of patent applications rather than a specialization in 4IR.
Keywords: 330